(3GdNdGa aj Gdabgs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3Ydj Hf dWa Gddg Hf YHO Gddgs)
(3ChdgG (B:s
(3eHJhQI GdChd, hChd GdehLhO efgG(B: (3hef hLO eGA GdHMQ agh hGLO ddeGA GdPj JfGhdg GdXGgQ hYdi GdeSCdI ELeGY GdaQbI(B...s
(3BNQgG (B:s
(3hOdjdfG ELeGY GdaQbI hWQjbI GdGMJjGW, hCNHGQge PcQfGgG aj GdcJGH GdebOe PcQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B84s
(3GdPQjYI(B:(3L(B7(3,U(B168(3,Qbe(B1137s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis